PRETRIAL PROBLEMS WITH THE OBJECT OF THE ESTABLISHMENT OF SUSPECTS - Wira Purwadi; Edi Gunawan (Jurnal Al-Dustur, 2021)
ABSTRACTUntil now, there has been no legal certainty for justice seekers through pretrial. The object of determining the suspect why when someone is declared a suspect then submits the Judge accepts a pretrial. Then the investigator can re-assign him a suspect so that the determination of the suspect occurs repeatedly. The Judge will also cancel the status of the suspect repeatedly and creates legal uncertainty. This study aims to determine pretrial executors to determine the suspect (Case Decision Study No: 3 / Pr/a.Pid / 2017 / PN.Gto) and Interpreting pretrial with the object of determining the suspect. This study uses normative research by using literature as the primary source. The results showed that pretrial executors with the object of determining the suspect (Case Decision Study No: 3 / Pra.Pid / 2017 / PN.Gto) is an example of a convoluted judicial process and does not provide legal certainty for a person because the applicant even though it has been three times the Judge receives the pretrial; the investigator is still returning to determine the applicant as a suspect. Interpreting a pretrial with the object of the determination of a suspect is difficult. Determining a suspect is not a straightforward job because it relates to a person's status before the law, so accuracy and prudence are needed to determine whether someone is worthy of being a suspect. An investigator may not use excessive authority in determining a person as a suspect because the implication of having a legal status can deprive someone of his right of independence as an arrest or detention.